Formação continuada na perspectiva colaborativa: subsídios para inclusão nas aulas de educação física - Oliveira, Ana Carolina Santana de (2017)
With the implementation of public policies related to school inclusion, particularly those targeted at the public of special education (PSE), number of students with special educational needs (SEN) enrolled in common classes’ increases. Physical Education, as a compulsory curricular component in Basic Education since the implementation of the National Education Guidelines Law (NEGL) in 1996, cannot fail to meet this student, especially those in a situation of inclusion in the regular classes, being one of the promoters within the daily school life with regard to conviviality and learning in diversity. From this perspective, several studies suggest the professional unpreparedness of teachers in relation to educational inclusion, either because they do not know how to deal with the deficiencies, or even because they are afraid to deal with the specificities of the students. Such professional unpreparedness is due to initial training or lack of continuing training, according to some recent research. Through this panorama, this research was based on collaborative teaching, which achieved promising results in promoting the inclusion of students with disabilities. Thus, the general objective of this research was to implement and evaluate a training program by means of collaboration for physical education teachers of regular schools in a medium-sized municipality in the interior of the state of Bahia. It was of the qualitative type that allows the deepening of a certain situation and direct contact of the researcher with the situation being investigated. After approval by the ethics committee, a survey was made of the existing schools in the municipality and according to the criteria established for inclusion in the survey, 14 schools were left 2 (one public and one private) that were selected. In these schools, 3 teachers with 5 PSE students were also selected. To carry out the training program, the research consisted of 3 stages. After the instruments were applied (interviews and questionnaire), six categories of analysis were obtained. Each category was analyzed qualitatively. As results achieved, the program was evaluated positively by teachers, understanding the importance of collaboration in their classes; and they have been able to understand that methodological modifications and adjustments are necessary for the effectiveness of school inclusion and that continuing education is necessary for pedagogical practices to be revised and modified towards the participation of all students. Collaborative work can achieve more positive results than if done individually, as long as there is involvement of all who directly benefit from this proposal, students and teachers. From the results achieved, it was possible to conclude that the participating teachers perceived the collaboration as positive, contributing significantly to overcome the challenges inherent in the practice of Physical Education, learning and participation of children with disabilities.